Design, synthesis, structure-activity relationship studies, and three-dimensional quantitative structure-activity relationship (3D-QSAR) modeling of a series of O-biphenyl carbamates as dual modulators of dopamine D3 receptor and fatty acid amide hydrolase - De Simone, A; Russo, D; Ruda, G; Micoli, A; Ferraro, M; Di Martino, R; Ottonello, G; Summa, M; Armirotti, A; Bandiera, T; Cavalli, A; Bottegoni, G (American Chemical Society, 2017)
We recently reported molecules designed according to the multitarget-directed ligand paradigm to exert combined activity at human fatty acid amide hydrolase (FAAH) and dopamine receptor subtype D3 (D3R). Both targets are relevant for tackling several types of addiction (most notably nicotine addiction) and other compulsive behaviors. Here, we report an SAR exploration of a series of biphenyl-N-[4-[4-(2,3-substituted-phenyl)piperazine-1-yl]alkyl]carbamates, a novel class of molecules that had shown promising activities at the FAAH-D3R target combination in preliminary studies. We have rationalized the structural features conducive to activities at the main targets and investigated activities at two off-targets: dopamine receptor subtype D2 and endocannabinoid receptor CB1. To understand the unexpected affinity for the CB1 receptor, we devised a 3D-QSAR model, which we then prospectively validated. Compound 33 was selected for PK studies because it displayed balanced affinities for the main targets and clear selectivity over the two off-targets. 33 has good stability and oral bioavailability and can cross the blood-brain barrier.